O atenuamento do princípio de não contradição aristotélico em “domínios contínuos” com relação à noção de instantes de tempo definidos como “pontos de acumulação” - Krewer, Karine (2012)
This study presents the hypothesis of relativizing the Principle of Non- Contradiction (PNC) from the definition of temporal moments as "accumulation points". Aristotle's PNC was examined by the mathematician Bernard Bolzano. Bolzano's considerations have set that in each part of the minimum time, ie at each instant of time, "can not assign two contradictory properties to the same object" thus, time resembles a straight line formed of points that follow one another. Viewed as cardinal units, the moments are already in the form of archetypal "geometrical points", which gives a character "spatialized" without the commitment to show up as a real image of the timestep (temporal moment) in its structure within the continuum of time. I show the notion of time "duration" of Henri Bergson allied to the notion of "accumulation point" of Georg Cantor, saying that time is like a "continuum set" that offers infinite points among its elements; the duration admits that time is continuous and undivided. Thus, by isolating a moment (an instant) from the other, we break up time into fragments. According to Bergson, this is not time but space. The scientific procedures measure the space when they claim to measure time. The temporal moments or timestep, which form the past, the present and the future times are so intertwined that they can not be separated under the faculty of memory that keeps them connected. Memory will be presented as a structure that allows "states-of-contradictory-things" to happen. These contradictions are understood here as phenomena that occur in regions of boundary, environment, neighborhood and movement. The Dialetheism is the thesis which states that dialethics (contradictions) occur in regions where the law of continuity is present. Graham Priest, creator of the thesis of Dialetheism allied, in his research, Hegel's definitions on contradiction as a fitment of life and ideas of Leibniz, on the law of Continuity. Contradictions appear then in the regions of neighborhood and motion from a state of things to another, where the law of continuity is present and the temporal continuum is considered a continuous set of infinite points.